Alcohol, drugs, and crime - Chalub, Miguel (2006)
Objective: This article describes two complex and doubly preoccupying situations in terms of public health, either, for its high prevalence and/or its consequences. These problems are the psychoactive substance use disorder and crime. The form will be told as diverse researchers associate them, as well as the situation of the exam of users and alcohol dependents and drugs. Method: A revision of publications was become fulfilled on the subject, using Medline and Lilacs as data bases, covering the period of 1986 the 2006. The keywords used had been: "Alcoholism", "drug dependence", "drug abuses" and "crime". Summaries of congresses, articles and excellent books on the subject, published for different authorities in the subject, in diverse phases of research, had been consulted and enclosed. Conclusion: The diverse research coincide in the affirmation of an association between psychoactive substances use disorders and crime. What it is possible to evidence is the high ratio of violent acts when the alcohol or the illicit drugs is used by aggressors, its victims or in both. When it carries through an expert examination in authors who allege some relation of the practiced act with alcohol consumption/drugs, this exam must take in consideration the substance in use, the clinical symptom for caused it, as well as verifying the presence of a diagnosis, the existence of causal nexus and possible alterations in the understanding capacity and/or determination of the agent.